Selected Persistent Organic Pollutants in Ambient Air in Turkey: Regional Sources and Controlling Factors - Gungormus, E.; Sofuoglu, A.; Celik, H.; Gedik, K.; Mulder, M.D.; Lammel, G.; Birgül, Aşkın (American Chemical Society, 2021)
As a result of its unique location, Turkey receives air masses from Europe, Russia, Middle East, and Africa, making it an important place in terms of long-range atmospheric transport (LRT) of contaminants. Atmospheric levels of 22 organochlorine pesticides (OCPs), 45 polychlorinated biphenyls (PCBs), and 14 polybrominated diphenyl ethers (PBDEs) were measured in two metropolitan cities, Istanbul and Izmir, on a weekly basis from May 2014 to May 2015. Dichlorodiphenyltrichloroethane (DDT) and its derivatives were dominant OCP species, followed by isomers of hexachlorocyclohexane (HCH) at both sites. The annual mean concentration of ?DDX (sum of o,p?-DDT, p,p?-DDT, o,p?-DDD, p,p?-DDD, o,p?-DDE, and p,p?-DDE) was 82 pg/m3 for Istanbul and 89 pg/m3 for Izmir, while these levels were about 46 pg/m3 for ?HCHs (sum of ?-, ?-, ?-, and ?-HCH) at both of the sites. At both stations, tri- and tetra-PCBs and tetra- and penta-PBDEs were dominant congeners. The temperature dependence indicates that both LRT and local contaminated areas contribute to the elevated levels. A Lagrangian particle dispersion model (FLEXPART) showed a few potential source regions in northern Africa and Middle East, southern-southwestern and eastern Europe including Russia, as well as from local domestic metropolitan areas. © 2021 American Chemical Society.
PubMed ID: 33475343
Keywords: active sampling; organochlorine pesticides (OCPs); particle dispersion modeling; polybrominated diphenyl ethers (PBDEs); polychlorinated biphenyls (PCBs); Turkey